Development of Geometry Analysis Using Geogebra Scripting in terms of Student Cognitive Capabilities. (April 2020) - Bernard, M; Setiawan, W
Abstract: Geometry is a part of mathematics related to points, lines, planes, flat buildings, and building spaces. And their thought processes must be discussed by students and mastered for geometry analysis. Students must have good analytical skills dealing with geometric questions based on cognitive abilities, namely understanding, connection, communication, reasoning, critical and creative, each of which has indicators as references using the Geogebra help software by Geogebra Script. The method used is a learning development model, and before using ICT media from 41 students, 85.36% participation in mastering vectors and 78.05% not mastering transformation geometry, and after using the inability of media to connect vectors and convert vectors to 48, 78% and 41.47%. And there was a significant increase before and after using media supported by GeoGebra scripts, namely the average grade from 29.88 to 58.29. Based on these results because there is an increase in the cognitive abilities of students who use Scripting Geogebra, however, there is a need to consider evaluating especially reasoning ability, problem-solving, and critical because the increase is below 50%.